Influential Social Workers: A Preliminary Exploration of Social Work Faculty - Geoffrey L. Greif; Harris Chaiklin; Stacy Timlin (Social Work & Society, 2011)
The profession of social work in the U.S. has been influenced and is being influenced by a wide-range of advocates, politicians, practitioners, and educators. This paper is a preliminary attempt to systematically examine who social work faculty consider influential in shaping the field. Identifying influential social workers is an important step in understanding the history of a profession, its current state, and its future trajectory.